2018
DOI: 10.1155/2018/7434536
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Natural Rubber‐Based Magnetorheological Elastomers at Large Strain for Base Isolators

Abstract: To withstand harsh conditions and have a moderate strength, it is desirable to use natural rubber for base isolators. In addition, previous studies have measured the magnetorheological (MR) effect under low-strain range, mostly within 10%. In the reality, it is necessary to evaluate the performance under large-strain range for base isolators. In this study, material properties of natural rubberbased MREs with various mixing ratios were evaluated under large-strain range (∼100%). In the first step, MREs with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Nearly all elastomer materials can be used for the matrix of the MRE composite. Natural rubber (NR), polyurethane (PU) and nitrile butadiene rubber (NBR) as well as thermoplastic elastomers (TPE) were already exploited for this purpose Hu et al, 2005;Lee et al, 2018). However, the most popular elastomer matrix for MRE is silicone rubber, because the preparation of the composite body is quite simple.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all elastomer materials can be used for the matrix of the MRE composite. Natural rubber (NR), polyurethane (PU) and nitrile butadiene rubber (NBR) as well as thermoplastic elastomers (TPE) were already exploited for this purpose Hu et al, 2005;Lee et al, 2018). However, the most popular elastomer matrix for MRE is silicone rubber, because the preparation of the composite body is quite simple.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that anisotropic MREs with greater iron particle volume fraction yield properties comparable to those of the isotropic MRE with the same particle volume fraction (Schubert and Harrison, 2015). Reported studies have also suggested that relatively small increase in the relative MR effect of the anisotropic MRE compared with those of the isotropic MRE, especially for relatively higher particle volume fractions of about 30% (Bellelli and Spaggiari, 2019; Lee et al, 2018). On the other hand, MREs containing <30% volume particle fraction may be damaged under the stress of the absorber mass or weight of structure that MRE is going to support (Lerner and Cunefare, 2007).…”
Section: Bi-directional Mre Isolator Designmentioning
confidence: 99%
“…Besides, many semi-active MRE-based vibration suppression devices have been designed for applications in structural seismic mitigation (Gu et al, 2016, 2017, 2019; Yu et al, 2016). Owing to the attractive potentials of MREs in vibration attenuation applications, considerable efforts have been made toward designing, fabricating, characterizations, and testing of MREs and MRE-based vibration isolators in recent years in order to seek guidance on their design for different vibration mitigation applications (Behrooz et al, 2016; Collette et al, 2010; Lee et al, 2018; Li and Li, 2015; Xin et al, 2016a; Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetorheological elastomers (MRE) are viscoelastic smart composites that show variable stiffness upon application of an external magnetic field. These compounds find applications in dampers for vibration absorption [ 1 , 2 ], in robotics, electronics [ 3 , 4 ], and force/acceleration sensors [ 5 , 6 , 7 ]. Depending on how magnetoactive particles are distributed in the matrix, two types of MRE are distinguished in literature: (1) isotropic MREs have homogeneously distributed particles within the matrix.…”
Section: Introductionmentioning
confidence: 99%